The effect of silent reading in improving the skill of understanding the read text among the seventh grade students in the Directorate of Education for the northeastern Badia region - العظامات, هايل (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The study aimed to identify the effect of silent reading on improving the skill of understanding the read text among seventh grade students in the Education Directorate of the Northeastern Badia region. To achieve this, a reading comprehension test was built. The study population consisted of seventh grade students in the Directorate of Education for the northeastern Badia region, while the study sample consisted of (56) seventh grade students in the Directorate of Education for the northeastern Badia region, distributed into two divisions in Umm Al Qateen Secondary School for Boys, so that the control group consisted of (27) students, They studied in the usual way, and the experimental group consisted of (29) students, who studied using the silent reading method, and a semi-experimental design based on a pre- and post-test was applied to the two groups. The results of the study showed that there were statistically significant differences between the average performances of the students of the study, due to the teaching method, in favor of the experimental group (silent reading). The study recommended the adoption of the silent reading method in developing reading comprehension skills when studying the Arabic language, as it has proven its effectiveness in the current study, and the need to identify the silent reading skills to be trained in each class and at every stage of education.